Pengaruh Corporate Social Responsibility (Csr) Terhadap Kesejahteraan Masyarakat Pada PT Indonesia Fibreboard Industry Tbk di Desa Mendis Jaya - Umi Muzakiyatul Laila; Sri Rahma; Rabiyatul Alawiyah (Pusat Riset dan Inovasi Nasional, 2026)
The implementation of Corporate Social Responsibility (CSR) continues to develop along with the growing awareness of companies toward community welfare. PT Indonesia Fibreboard Industry Tbk (IFI), located in Mendis Jaya Village, Musi Banyuasin Regency, carries out various CSR programs in the fields of education, economy, and health aimed at improving community welfare. CSR plays an essential role not only as a form of social responsibility but also as a strategy to build harmonious relations between the company and the community. This study employed a quantitative method with 98 respondents who are beneficiaries of PT IFI’s CSR programs. The results show that CSR in the fields of education and economy has a positive effect on community welfare, while CSR in health has no significant effect. Simultaneously, the three CSR fields contribute 21% to community welfare, indicating that other factors 79% outside beyond CSR also influence welfare in Mendis Jaya Village